Synthesis of nano-capsules via aqueous emulsion RCMP-PISA and encapsulation - Sarkar, Jit (2020)
Biocompatible nano-capsules (polymer vesicles) were prepared by combining NaI-catalyzed living radical polymerization with aqueous emulsion PISA (polymerization induced self-assembly). Poly(ethylene glycol) methyl ether methacrylate (PEGMA) and methyl methacrylate (MMA) were used as hydrophilic and hydrophobic monomers, respectively. Spheres and vesicles were generated depending on the degrees of polymerization of the hydrophilic and hydrophobic segments in the block copolymers. The spheres and vesicles were crosslinked using a divinyl monomer (ethylene glycol dimethacrylate (EGDMA)) as a co-monomer of MMA in situ during the polymerization. The encapsulation ability of the obtained vesicle was studied using a hydrophilic dye, i.e., rhodamine-B.